(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article is devoted to the analysis of the use of sentences in the novel "Adil-Maria" by the writer Shakarim Kudaiberdiev, who continues the traditions of Abai and is distinguished by his original writing style and philosophical motives. In Kazakh linguistics, there is a small number of scientific works devoted to the study of the language of Shakarim's works. These works are mainly devoted to the study of the poet's poems. However, the linguistic features of the prose work "Adil-Maria", called the "tragic novel", including its use of sentences, have not yet been the subject of research. The purpose of the study is to group sentences in a novel depending on the purpose of the utterance, to determine the characteristics of the character's language and the author's style. During the analysis, the main scientific and theoretical works on Kazakh linguistics were used, linguistic units in declarative, exclamatory, imperative, interrogative sentences were considered. When analyzing the language of the work, the author's use of sentences that realistically reflect the Kazakh life of the early twentieth century, methods of description, explanation, lexico-semantic methods, etc. were used. The results of the research can be used in the study of such disciplines as "Introduction to linguistics", "Syntax of the Kazakh language", "Linguistic analysis of literary text", taught in universities, and in classes on "Shakarim studies", "History of the Kazakh literary language", studied as an elective. The article is addressed to philologists, the general public interested in the study of the Kazakh language and Shakarim's work.